Self-reported Anxiety and Coping: A Cross-Sectional Study among Saudi Nursing Students during COVID-19 Pandemic using GAD-7 and Briefcope - Asad, Mohammed; Alenezi, Atallah; Alsalowly, Mohammed Nasser; Asdaq, Syed Mohammed Basheeruddin; Alamri, Abdulhakeem S.; Alsanie, Walaa F.; Alhomrani, Majid; Mohzari, Yahya; Alrashed, Ahmed; Shammakhi, Ibraheem N.; Almutairi, Muath F.; Aldhawyan, Norah N.; et al. (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Anxiety is seen among students even during normal times. The COVID 19pandemic is believed to have increased anxiety and depression among the students. Purpose: An investigation was done to assess the anxiety levels and coping strategies of nursing students in Saudi Arabia. The influence of demographics on the anxiety levels and coping strategies were also determined. Methods: A cross-sectional study was conducted using a questionnaire through Google forms. The questionnaire had items related to demographics such as age, sex, etc., along with a question to know about the confidence of students to work as nurses. A GAD-7 scale was used to assess anxiety levels and BriefCope was used to determine coping strategies. Statistics were performed using non-parametric tests, factorial analysis, and linear regression. Results: More than half of the participating students experienced moderate to severe anxiety. The anxiety levels were not influenced significantly by demographics except the young age. More than 50% of the students were reluctant to work as nurses and this affected the anxiety score significantly. Factorial analysis grouped variables into six factors. Linear regression showed a positive correlation of these factors with anxiety. Conclusion: Anxiety score revealed that Saudi nursing students had moderate to severe anxiety. The combined number of students reluctant or scared to work was more than those who were confident to work as nurses. A positive association was observed between factor variables with mild and moderate anxiety.
Keywords: Anxiety; Coping strategy; Factorial analysis; linear regression; Variance; nursing students